Comparative prevalence of adenomatous polyps in people aged 45 to 49 years and in people over 50 years of age in a Colombian population: a case-control study - Guzmán Calderón, Edson (2022)
Introduction: This article summarizes the clinical practice guide (CPG) for the diagnosis and management of cholelithiasis, acute cholecystitis and choledocholithiasis in the Peruvian Social Security (EsSalud). Objective: To provide clinical recommendations based on evidence for the management of patients with cholelithiasis, acute cholecystitis and choledocholithiasis in EsSalud. Methods: a guideline task force (GTF) was formed with internists, general surgeons, gastroenterologists, and methodologists. The group proposed 10 clinical questions to be answered in this Clinical practice guideline (CPG). Systematic searches of preview reviews were performed and when it was necessary, primary studies from PubMed and CENTRAL during 2017 were reviewed. The evidence was selected aiming to answer each proposed question. Certainty of evidence was evaluated using Grading of Recommendations Assessment, Development, and Evaluation (GRADE) methodology. In periodical work sessions, the group used GRADE methodology for reviewing the evidence and formulating recommendations, good clinical practice items and three flowcharts for diagnosis and treatment. Finally, the CPG was approved by Resolution Nº 046-IETSI-ESSALUD-2017. Results: This CPG approached 10 clinical questions divided into two topics: diagnosis and management. Based on these questions; one strong recommendation, five weak recommendations, and 17 good clinical practice items and three flowchartser abstracts the methodology and evidence-based conclusions of the CPG for diagnosis and management of cholelithiasis, acute cholecystitis and choledocholithiasis in EsSalud.